Persepsi Masyarakat terhadap Kualitas Pelayanan di Terminal Arjosari Kota Malang: Public Perception of Service Quality at Arjosari Terminal Malang City - Maskan, Mohammad; Utaminingsih, Alifiulahtin; Soepeno, Bambang (Universitas Muhammadiyah Sidoarjo, 2014)
This study aims to analyze the quality of service in Arjosari Bus Station Malang. The service quality theory used in the study refers to the opinion of Tjiptono (2000) which consists of: physical evidence (tangibility), reliability, responsiveness, assurance, and empathy. The study uses a descriptive approach, by taking a sample of 30 service users of Arjosari Bus Station Malang. While, the methods of analysis use the mean. The results show that the quality of service in Arjosari Bus Station Malang is good enough with an average score of 2.86. However, to improve the quality of service to the service users of the bus station, then there are several things that must be done by the local government of Malang, ie: adding free WIFI facility in bus station, fixing the layout and the exterior rooms of the bus station, and improving the room's cleanliness and coolness at the bus station environment. Furthermore, it also improves the reliability in service, such as: the simplicity for the bus station service users to consult with officials and leaders where necessary to the provision of the excellent service.